2018
DOI: 10.1073/pnas.1803377115
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-378 promotes autophagy and inhibits apoptosis in skeletal muscle

Abstract: The metabolic regulation of cell death is sophisticated. A growing body of evidence suggests the existence of multiple metabolic checkpoints that dictate cell fate in response to metabolic fluctuations. However, whether microRNAs (miRNAs) are able to respond to metabolic stress, reset the threshold of cell death, and attempt to reestablish homeostasis is largely unknown. Here, we show that miR-378/378* KO mice cannot maintain normal muscle weight and have poor running performance, which is accompanied by impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(90 citation statements)
references
References 50 publications
4
83
0
3
Order By: Relevance
“…In this study, we have demonstrated that miR-378d plays an important role miR-378d was demonstrated to play a critical role in M. tb-infected macrophages through its target, Rab10, and findings contributed to elucidation of the mechanism underlying miRNA activity in host defense or M. tb pathogenesis during M. tb infection. As introduced previously, miR-378 family members are reported to be induced or inhibited in some tumors and cancers to regulate autophagy (Li et al, 2018b), apoptosis (Costantino et al, 2016;Kuang et al, 2016;Lei et al, 2018;Li et al, 2018b;Ma et al, 2019), cell migration (Ma et al, 2014;Kuang et al, 2016;Templin et al, 2017;Ho et al, 2018), cell proliferation, etc. (Zhang et al, 2017b(Zhang et al, , 2019Li et al, 2018a).…”
Section: Discussionmentioning
confidence: 87%
“…In this study, we have demonstrated that miR-378d plays an important role miR-378d was demonstrated to play a critical role in M. tb-infected macrophages through its target, Rab10, and findings contributed to elucidation of the mechanism underlying miRNA activity in host defense or M. tb pathogenesis during M. tb infection. As introduced previously, miR-378 family members are reported to be induced or inhibited in some tumors and cancers to regulate autophagy (Li et al, 2018b), apoptosis (Costantino et al, 2016;Kuang et al, 2016;Lei et al, 2018;Li et al, 2018b;Ma et al, 2019), cell migration (Ma et al, 2014;Kuang et al, 2016;Templin et al, 2017;Ho et al, 2018), cell proliferation, etc. (Zhang et al, 2017b(Zhang et al, , 2019Li et al, 2018a).…”
Section: Discussionmentioning
confidence: 87%
“…MiR-21 targeted and suppressed the peroxisome proliferatoractivated receptor (PPAR) transcript, which regulates plays an important regulatory role in inflammation, ATH, tumors, and fatty acid anabolic, was shown to be increased during HF (Lai et al, 2015;Pinti et al, 2017). Overexpression of miR-378 suppressed ATP synthase F0 subunit 6 (ATP6) and was characterized in the interfibrillar mitochondria amidst diabetes mellitus (Jagannathan et al, 2015;Shepherd et al, 2017;Li et al, 2018). Recent studies showed that cardiopulmonary exercise test was fairly able to elevate the serum levels of miR-21, miR-378, and miR-940 in HF patients (Xu et al, 2016).…”
Section: Exercise Mediates Protection Against Hfmentioning
confidence: 99%
“…It has been estimated that miRNAs regulate the activity of 30%‐50% of protein‐coding genes and modulate about 10%‐30% of human genome expression . miRNAs play a role in regulating various biological processes including metabolism, cell proliferation and differentiation, and apoptosis . The function of miRNA is directly associated with structure; thus, analysing the process of miRNA biogenesis may provide new ideas for the study of miRNA.…”
Section: Overview Of Mvs and Mirnasmentioning
confidence: 99%
“…44 miRNAs play a role in regulating various biological processes including metabolism, cell proliferation and differentiation, and apoptosis. [45][46][47] The function of miRNA is directly associated with structure; thus, analysing the F I G U R E 1 The process of MV formation and release from cells. External stimuli followed by increasing intracellular Ca2+ that inhibits the flippase and activates floppase and scramblase with PS movement from the inner face to the outer face of cell membrane.…”
Section: Mirnasmentioning
confidence: 99%